BETWEEN IMITATION AND RESISTANCE: EARLY INDIAN ENGLISH LITERATURE UNDER BRITISH COLONIAL RULE - Vishvanath; Kantharaja K P (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This article explores the complex evolution of early Indian English literature during the British colonial period, focusing on the thematic tension between imitation and resistance. Introduced through colonial education policies such as Macaulay’s Minute of 1835, English became both a tool of imperial control and a medium for Indian self-expression. Early Indian writers, shaped by missionary and colonial institutions, initially adopted Western literary forms and language, imitating British models in poetry, prose, and narrative structure. However, this phase of imitation gradually gave way to nuanced forms of resistance, as Indian authors infused their works with indigenous themes, cultural pride, and social critique. Through hybrid literary expressions that merged Indian traditions with English idioms, writers negotiated between two worlds—asserting native identity while engaging with colonial modernity. This hybrid voice laid the foundation for a transition toward nationalist literature in the late 19th and early 20th centuries, where English was used more assertively to challenge colonial ideologies and articulate visions of independence. The article concludes that early Indian English literature, though born in the crucible of colonialism, played a vital role in shaping India’s literary and political awakening, leaving a lasting legacy in the canon of postcolonial literature.